PENGARUH FASILITAS BELAJAR, KECERDASAN EMOSIONAL DAN KREATIVITAS GURU TERHADAP EFEKTIVITAS BELAJAR SISWA SDN BINUANG 4 KABUPATEN TAPIN - Mahrita Mahrita; Rosadiro Cahyono (STIE Mahardhika, 2022)
This writing starts with a theoretical framework, expert opinion, or the researchers' knowledge based on their experiences, and then progresses to challenges with proposed solutions in order to seek justification (verification) in the form of empirical data support in the field. The goal of this study is to determine the degree to which learning facilities, emotional intelligence, and teacher creativity contribute to the effectiveness of students at SDN Binuang 4 Tapin Regency. The study takes a quantitative approach, with a 34-person population, a 34-person sample size, and data analysis processes. The findings of this study indicate that the variables Learning Facilities, Emotional Intelligence, and Teacher Creativity all have an effect on the Learning Effectiveness of students at SDN Binuang 4 Tapin Regency, that each of these independent factors has a substantial influence on the dependent variable continuously (simultaneously), and that the variable with the greatest effect on the dependent variable concurrently is the variable with the greatest effect on the dependent variable concurrently (simultaneously).